1995
DOI: 10.1007/bf01275212
|View full text |Cite
|
Sign up to set email alerts
|

Induction of HPRT- mutants in Chinese hamster V79 cells after heavy ion exposure

Abstract: The induction of resistance to 6-thioguanine by heavy ion exposure was investigated with various accelerated ions (oxygen-uranium) up to linear energy transfer (LET) values of about 15,000 keV/microns. Survival curves are exponential with fluence; mutation induction shows a linear dependence. Cross-sections (sigma i: inactivation, sigma m: mutation) were derived from the respective slopes. Generally, sigma i rises over the whole LET range, but separates into different declining curves for single ions with LET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is often reported that the frequency of deletion is higher for high LET radiation than for low LET radiation (Schwartz et al, 1994;Stoll et al, 1995;Zhu et al, 1995;Suzuki et al, 1996). On the contrary, some researchers reported that no significant difference on the frequency of deletions was observed between high LET and low LET radiation-induced mutants (Thacker, 1986;Aghamohammadi et al, 1992;Jostes et al, 1994, Bao et al, 1995Yamada et al, 1996).…”
mentioning
confidence: 96%
“…It is often reported that the frequency of deletion is higher for high LET radiation than for low LET radiation (Schwartz et al, 1994;Stoll et al, 1995;Zhu et al, 1995;Suzuki et al, 1996). On the contrary, some researchers reported that no significant difference on the frequency of deletions was observed between high LET and low LET radiation-induced mutants (Thacker, 1986;Aghamohammadi et al, 1992;Jostes et al, 1994, Bao et al, 1995Yamada et al, 1996).…”
mentioning
confidence: 96%
“…The literature data available for the quality of HPRT gene mutations induced by heavy accelerated ions are very scarce. A number of articles describe the mutational spectra induced by IR, which seems to be different in dependence on the type of radiation used: several about the effects of sparsely ionizing radiation (X-ray, gamma rays): [8,11,[19][20][21][22][23][24]; a few using alpha particles (or He ions): [5,11,14,20,25,26]; but only a couple exposing the cells to heavy charged ions: [8,21,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly for accelerated heavy ions, Baumstark-Khan et al reported the number of total deletions of the HPRT gene increasing with LET of accelerated oxygen ions up to approximately 318 keV/ μm followed by decrease, while the number of partial deletions was changing mildly in the same LET interval. It has been shown that even heavy ions can cause small alterations or point mutations [27], possibly due to the created secondary electrons. The results of HPRT gene molecular spectra induced by different ion species show high level of heterogeneity.…”
Section: Introductionmentioning
confidence: 99%